Strategi Desain Kemasan untuk Meningkatkan Kepatuhan Penggunaan Obat pada Pasien dengan Penyakit Kronis dan Infeksi - Amaliya Bunga Dwiyanti (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Patient adherence to medication regimens is a crucial factor in achieving therapeutic success, especially in chronic diseases such as diabetes mellitus and hypertension, as well as infections like tuberculosis. Low adherence can lead to complications, treatment failure, and a potential increase in antimicrobial resistance. This study reviews various interventions and factors affecting medication adherence. Through an analysis of six scientific articles, it explores the effectiveness of calendar packaging, pill boxes, poster media, and technology-based interventions in improving adherence. In addition, patient characteristics, including gender, age, education level, occupation, and comorbidity, are also analyzed to understand their contribution to adherence. The results indicate that structured and personalized interventions, often supported by technology, have significant potential to improve patient adherence. However, effective implementation requires a deep understanding of patient characteristics and adaptation to individual needs. These findings are expected to provide insight for healthcare providers in designing more effective intervention strategies to improve patient adherence and health outcomes.